2014
DOI: 10.2337/db14-0375
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Reverses the High-Fat Diet–Induced Increase in Brain Aβ and Improves Memory in an Animal Model of Alzheimer Disease

Abstract: Defects in insulin production and signaling are suspected to share a key role in diabetes and Alzheimer disease (AD), two age-related pathologies. In this study, we investigated the interrelation between AD and diabetes using a high-fat diet (HFD) in a mouse model of genetically induced AD-like neuropathology (3xTg-AD). We first observed that cerebral expression of human AD transgenes led to peripheral glucose intolerance, associated with pancreatic human Aβ accumulation. High-fat diet enhanced glucose intoler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
207
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(231 citation statements)
references
References 78 publications
(83 reference statements)
20
207
4
Order By: Relevance
“…Ghanim and Dandona for their comments (1) on our article (2). Their results showing that insulin infusion leads to decreased expression of amyloid precursor protein (APP) and presenilins in human monocytes (3) are in line with reports in cell culture (4) and support the use of insulin in Alzheimer disease (AD) (5).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Ghanim and Dandona for their comments (1) on our article (2). Their results showing that insulin infusion leads to decreased expression of amyloid precursor protein (APP) and presenilins in human monocytes (3) are in line with reports in cell culture (4) and support the use of insulin in Alzheimer disease (AD) (5).…”
supporting
confidence: 67%
“…The other key mechanism by which cerebral Ab concentrations are regulated is through brainblood clearance. Indeed, we found a coinciding increase in plasma Ab concentrations minutes after the systemic insulin administration (2). Although data directly confirming that insulin triggers a rapid Ab efflux via the blood-brain barrier are still lacking, higher cerebral blood flow (7) and cerebrospinal fluid Ab levels (8) have been reported 30 and 120 min after the administration of insulin, respectively.…”
mentioning
confidence: 67%
“…Numerous studies in various animal models have shown that diet (HF diet/sucrose/fructose) or chemical (administration of the β-cell toxin streptozotocin (STZ)) induced diabetes promote, tau phosphorylation, and synaptic/neurodegeneration 23,[43][44][45][46][47] . The potential mechanisms may involve neuroinflammatory and oxidative stress mechanisms 14 .…”
Section: Discussionmentioning
confidence: 99%
“…22). Further, recent evidence indicates β-cell dysfunction in AD rodent models 23,24 and that Aβ and Tau have been shown to accumulate in human post-mortem pancreatic tissue in T2D 25 , possibly contributing to β-cell dysfunction. Despite this evidence, there is a lack of literature investigating pancreatic β-cell activity (HOMA-B) on cognition and AD related pathology.…”
Section: Growing Evidence Supports the Hypothesis That Type 2 Diabetementioning
confidence: 99%
“…In a recent issue of Diabetes, Vandal et al (1) showed that the administration of a high-fat diet induced the deposition of b-amyloid in the brains of mice. They also showed that the deposition of amyloid was prevented or reversed by the administration of insulin.…”
mentioning
confidence: 99%